Balloon leakage dilation over arterio-aorta rail support greatly facilitates a complex aortic paravalvular leak closure - Maria Onorato, Eustaquio; Carasi, Massimo; Zadro, Mirko; Cucchini, Umberto; Chirillo, Fabio (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
In patients with an aortic paravalvular leak (PVL), the retrograde femoral arterial approach is most commonly used [1, 2]. Nevertheless, in some cases an antegrade (via trans-septal puncture) or a retrograde transapical approach may be alternative options [3]. Particularly for the anatomically hard-to-approach calcified serpiginous tracts where an extra support is needed, an arterio-arterial loop can be established and may be key for a successful procedure [4].